The effects of a mindfulness-based program on higher education students - Serrão, Carla; Rodrigues, Ana Rita; Ferreira, Tiago (Frontiers in Education, 2022)
Background: Entering higher education is a process with multiple challenges that requires the mobilization of personal, social and instrumental resources. As a result, students tend to experience grater stress, anxiety and depression. In this regard, mindfulness-based interventions can serve as a useful tool to help students deal with these demands. Objective: This study aimed to evaluate the effect of a Mindfulness in Education program in reducing stress, anxiety and depression symptoms among students. Methods: Forty-four students of higher education from four degrees in the fields of Social and Cultural Sciences participated and finished surveys before and after the 12-weeks intervention, measuring stress, depression, anxiety, mindfulness, and self-compassion. Twenty-three students (82.61% female; Mage = 20.35 DPage = 3.24) participated in Mindfulness in Education. These participants were paired with twenty-one students (90.48% female; Mage = 18.67, DPage = 0.73), which constituted the control condition. Results: The results showed a session x condition interaction that was statistically significant for depression (p <.012) and stress (p <.026). In the follow-up exploration, the experimental condition revealed a statistically significant and moderate change in the severity of the symptoms of depression (t(14) = -2.315, p = .036,  = .304, IC95%[-.023 – .499]) but not at the stress level (t(14) = -1.443, p = .171,  = .223, IC95%[-.006 – .364]). Conclusions: Outcomes were promising, adding to evidence that mindfulness-based interventions can play an important role in helping students manage stress and depression. However, it is still necessary to investigate the mechanisms underlying this type of interventions.